PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMAS GKPI PADANG BULAN - Citra Simatupang; Mukhtar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aimed to develop students’ ability to solve mathematical problems by applying the Contextual Teaching and Learning approach with the support of GeoGebra in a Statistics lesson for Grade X-1 at SMAS GKPI Padang Bulan. The study was conducted in two cycles, each involving stages of planning, implementation, observation, evaluation, and reflection. Students’ performance was assessed by comparing their actual scores to the maximum possible score, with results classified into qualitative levels. A class was considered successful if at least 80% of the students reached a moderate or higher category. Findings revealed a significant improvement in average scores: from 41 in the pre-test, to 63.2 in the first cycle, and 81 in the second cycle. The percentage of students reaching the minimum mastery level rose from 12% to 84%. Additionally, teacher performance in managing the learning process improved, with observation scores increasing from 3.08 to 3.5, classified as good. These results indicate that the use of Contextual Teaching and Learning supported by GeoGebra effectively enhances students’ mathematical problem-solving abilities.